Professional patienthood and mortality: Seán Ó Ríordáin's diaries 1974–1977. Issue 2 (5th January 2016) - Breathnach, Ciara
Abstract : Unwieldy by nature, unsolicited diaries and their study, this article contends, have the potential to offer deeper insights into the experience of illness but only if they receive due consideration from scholars. This article uses a series of historic diaries to examine the concept of 'professional patienthood' or being a full-time patient, and, while it found the narrative medicine approach to be very useful, it also found it limiting. The recent methodological trends in biomedicine and social sciences towards structured mechanisms like questionnaires—surveying and evaluating performance, satisfaction and experience—can only go so far. This article makes a case for the unsolicited, the unorthodox and the unstructured.